GERMINATION AND VIGOR OF MAIZE HYBRIDS SEEDS SUBMITTED TO WATER STRESS - de Castro Pias, Osmar Henrique; Melo Damian, Junior; Alba, Fabiano; Giacomelli, Aleixon Henrique; Lowe, Marcio André; Testa, Valéria (Acta Iguazu, 2000)
The water stress is the most limiting factor for germination of maize seeds, in this sense, to know more tolerant hybrids to this factor is essential for productive sustainability of the culture. The objective of this study was to evaluate the seed germination and seedling growth of maize hybrids submitted to water stress. The study was conducted in a completely randomized design in a factorial arrangement 4 x 5, with 8 repetitions. The first factor was composed of hybrids AS 1551, AG 5011, AG 8011 and CD 384. The second factor was the osmotic potential of 0.0, -0.4, -0.8, -1.2 and -1.6 MPa, obtained from KCl solutions applied to the seeds in order to simulate the water stress. It was determined the hard and dead seeds percentages, normal and abnormal seedlings, besides the length and dry mass of aerial and radicular part. The osmotic potential of -0.8 MPa completely inhibited the formation of normal seedlings in all hybrids. The reduction of osmotic potential of 0.0 to -0.4 MPa caused a reduction in the number of normal seedlings and dry mass production of aerial part. However, it increased the dry mass production of roots. In descending order of classification the hybrids that presented higher tolerance to water stress are AS 1551> AG 5011> CD 384> AG 8011.